STRATEGI PEMENANGAN PASANGAN KHAMAMIK-ISMAIL ISHAK DALAM PILKADA MESUJI TAHUN 2011 - Anggi E Zamora; Turtiantoro .; Lusia A (Journal of Politic and Government Studies, 2015)
This study analyzes the political strategies used by Khamamik-Ismail Ishak in thegeneral election of regional heads in Mesuji District. This is the first experience MesujiDistrict implement local elections. How Khamamik-Ismail Ishak strategy at regional headelections in 2011 so as to win the number of votes?In this study, researchers used a qualitative approach that will generate descriptivedata. This research was conducted in the District Mesuji. The data were obtained throughinterviews with Fuad Amarulloh as a successful team leader Khamamik-Ismail Ishak, winningteam and community, as well as data obtained from dokementasi.The strategy used in the general election of regional heads of Mesuji in 2011 carriedout in the form of the election campaign strategy, knowing the behavior of voters, as well asapproaches and political communication. The success of this strategy is able to win a pairKhamamik-Ismail Ishak to acquire 39 637 (39.75%) votes, defeating the pair Iskandar Malikiand Agus setio with 37 865 (38.17%) votes, Suprapto and Daryanto Dahlir with 10,161(1024%) voice, Bukhari Abdul Shomad and Paidi with 9905 (9.88%) and Arif Budiman andYedi Supriyatna with 1,961 (1.94%).Keywords: Regional